Hubungan Antara Kepadatan Penduduk dengan Kejadian Pneumonia Balita di Provinsi Bali Tahun 2021-2023 - Bella Ainur Rokhma (Pusat riset dan Inovasi Nasional, 2025)
Pneumonia remains one of the leading causes of mortality among children under five years old worldwide. Population density is presumed to be one of the factors influencing pneumonia incidence, particularly in regions with high population growth and mobility, such as Bali Province. This study aimed to analyze the relationship between population density and pneumonia incidence among under-five children in Bali Province during the 2021–2023 period. This research was a descriptive quantitative study with a correlational design. Data on population density and under-five pneumonia cases were obtained from reports by the Bali Provincial Health Office and the Central Bureau of Statistics (BPS). Spatial visualization was performed using Epi Map version 7.2.5.0, and correlation analysis was conducted using R Studio. Descriptive analysis showed an increase in both population density and the number of under-five pneumonia cases in Bali Province during 2021–2023. Population density rose from 11,641 people/km² to 12,096 people/km², while pneumonia cases increased from 2,677 to 5,743. However, Spearman correlation analysis indicated no statistically significant relationship between population density and pneumonia incidence, with rho values of 0.5667 and p-values of 0.1206 for 2021 and 2022, and a rho of 0.2333 with a p-value of 0.5517 in 2023 (p > 0.05). No significant relationship was found between population density and pneumonia incidence among children under five in Bali Province.